Asia-Pacific financial markets integration, innovation and challenges - Kim, Suk-Joong; McKenzie, Michael D., Prof (Emerald, 2007)
This volume of International Finance Review focuses on the Asia-Pacific financial markets. A total of 22 original papers, not published elsewhere, have been selected from a competitive field. These papers utilize a variety of methods, including theoretical, empirical and qualitative to highlight a range of issues across the region. Several papers offer combinations of these different categories and among the empirical papers, there are a wide variety of datasets analyzed. While China does play a significant part in the analysis of five of the papers in this volume (this is to be expected given its importance in the region), a host of other countries are also considered. This ensures the volume is truly international in its scope. These papers each serve to contribute to the knowledge on a particular issue related to the financial markets within this region and for this volume, three main issues have been identified: integration, innovation and challenges. Articles are contributed by experts in their fields. It is truly international in scope.
Keywords: Finance -- Asia.; Finance -- Pacific Area.; Asia -- Economic policy.; Pacific Area -- Economic policy.; elektronické knihy; electronic books